Racially liberatory pedagogy: a Black Lives Matter approach to education. Issue 9 (21st October 2019) - Castillo-Montoya, Milagros; Abreu, Joshua; Abad, Abdul
Abstract: In this study, we sought to understand how Black lives matter (BLM) epistemology, as displayed through six months of social media content from official accounts, can inform a racially liberatory pedagogy in higher education for Black and other racially minoritized students. We found BLM, through Facebook and Twitter, situated intersectional Black culture in the contemporary struggle for liberation. BLM also offered information that can raise its followers' intersectional critical consciousness. Additionally, BLM content highlighted actions that can support Black liberation. Lastly, BLM content supported the building of relationships and naming of emotions as Black people work toward their liberation. In this sense, BLM connected with elements of a racially liberatory pedagogy and offered nuances that advanced the framework. We discuss the implications of this framework for teaching in higher education.